PENGARUH IKLAN, KEPERCAYAAN MEREK DAN CITRA MEREK TERHADAP MINAT BELI KONSUMEN PENGGUNA HANDPHONE OPPO DI KOTA BIMA - NURIDA NATSIR; SRI ERNAWATI (Universitas Muhammadiyah Luwuk Banggai, 2020)
This study aims to determine whether the advertising variables, brand trust and brand image partially and simultaneously affect Oppo Mobile Consumer Interest of buying in the City of Bima. This study uses survey design on respondents by distributing questionnaires to 96 people. The population in this study is not measurable (Unknown population). The sample was 96 people with accidental sampling technique. data collection using a questionnaire with a Likert scale, observation, literature study . Data analysis using the validity test, reliability test, multiple linear regression, t test and F test using SPSS 20.00. The results show that Advertising (X1) influences Consumer Purchase Interest, Brand Trust (X2) does not affect Buy Interest, Brand Image (X3) influences Consumer Buying Interest and together Advertising (X1), Brand Trust (X2), Brand Image (X3) influences Interest of Buying